REMOTE AND RURAL: THE FORGOTTEN INEQUITY. Issue 1 (1st March 2013) - Layden, J; Bunch, H; Hekerem, D; Millar, L; Maxwell, V
Abstract : Introduction: Remote rural Scotland is 18% of the population and 94% of the land mass. With a lower demand for specialist healthcare, patients are at significant risk of being hidden and forgotten. Barriers to equitable access in remote rural communities includes: poor transport infrastructure, lack of OOH cover and recruitment from a limited pool. Aims and Methods: Innovative service models have been developed in partnership with NHS Boards to address the palliative care needs of Scotland's remote and rural communities. Service models deliver improvements to the quality of end of life care, increase the number of patients dying in their preferred place and reduce unplanned hospital admissions. Two examples are presented. Results: Optimal Utilisation of remote rural Resources (Argyll and Bute) involves a bank of Marie Curie nurses working to a more flexible contract, complementing existing staff to enable a fast, local and consistent response to palliative care needs. Staff receive some online training which overcomes the difficulties in arranging training within remote rural services. Blended Multi-visit model (Deeside)—a shared community nursing and Marie Curie role, with the flexibility for staff to split their time between a generalist and specialist palliative care role. This enables the service to meet patient needs whilst minimising staff travelling time. Conclusions: The service models focus on integration and partnership, which takes account of a less predictable demand, the geography and capitalising on the limited local resources. A complete understanding of remote rural communities is essential to develop innovative palliative care services that respond to patient needs.